Impact of DAA Treatment on Cardiovascular Disease Risk in Chronic HCV Infection: An Update - Roguljic, Hrvoje; Nincevic, Vjera; Bojanic, Kristina; Kuna, Lucija; Smolic, Robert; Vcev, Aleksandar; Primorac, Dragan; Vceva, Andrijana; Wu, George Y.; Smolic, Martina (Frontiers in Pharmacology, 2021)
Hepatitis C virus (HCV) infection is a systemic disease associated with multiple significant extrahepatic manifestations. Emerging studies indicate association between the HCV infection and a higher incidence of major adverse cardiovascular events such as: coronary artery disease, heart failure, stroke and peripheral artery disease, when compared to general population. Atherosclerosis is a common pathophysiologic mechanism of cardiovascular disease (CVD) development which is the leading cause of mortality in the Western world. Proposed mechanisms of HCV-induced atherosclerosis includes systemic inflammation due to the chronic infection with increased levels of pro-atherogenic cytokines and chemokines. Furthermore, it has been demonstrated that HCV exists and replicates within atheroschlerotic plaques, supporting the theory of direct pro-atherogenic effect of the virus. Direct acting antiviral agents (DAAs) represent a safe and highly effective treatment of HCV infection. Beside the improvement in liver-related outcomes, DAAs exhibit a beneficial effect on extra-hepatic manifestations of chronic HCV infection. Recently, it has been shown that patients with chronic HCV infection treated with DAA-based therapeutic regimes had a 43% reduction of CVD events incidence risk. Moreover, eradication of HCV with DAAs results in a significant positive effect on risk factors for cardiovascular disease, despite a general worsening of the lipid profile, . This positive effects is mainly due to an improvement of endothelial function and glucose metabolism. Although DAA treatment is associated with a beneficial impact on cardiovascular events, further studies are needed to fully elucidate the mechanisms responsible.